Autoestima e depressão em mulheres portadoras de vitiligo - Ruiz, Larissa Pires (2016)
Vitiligo is a depigmentation’s disorder of the skin, with an incidence of up to 2% of the population, particularly among female population. Investigations, both nationals and internationals, have pointed out that women suffering from this disease presented low selfesteem and high rates of depression. This study aimed to: 1) examine the occurrence of psychiatric morbidity in patients with vitiligo; 2) identify the severity of discomfort attributed to the presence of spots in different body regions; and 3) correlating discomfort attributed to the location of the spot, self-esteem, psychiatric comorbidities in general, and particularly of depression. For gathering information was used an online questionnaire, constructed and available in Google Docs base. Adults women diagnosed with vitiligo were invited to participate in the study, mainly through social networks and websites that offer information about the disease. The questionnaire presented initially the Informed Consent of the Research and, in the sequence, introduced issues related to socioeconomic variables and of living with the disease, namely: gender, age, education, occupation, marital status, family income; When he was diagnosed, the specialty of the professional that closed this diagnosis, among others. It was requested to indicate the body´s regions affected by stains and the degree of distressed related to each of them. Three instruments were available to assess various psychological conditions, namely: 1) Transversal Inventory PROMIS Level 1 for adults which assess risks related with mental health’s of 13 disorders; 2) Transversal Inventory PROMIS Level 2 Depression; and, 3) Self-Esteem Rosenberg Inventory. The participants presented aged 16-64 years, and the majority was declared single (41%), white (54.7%), with family income equal to or less than three minimum wages (38.7%), living in different regions of the country. The diagnosis would have happened 10 years or less (41.9%), by professional dermatologist (115 participants). 42.7% of the participants showed signs of depression, 50.4% showed the occurrence of six or more symptoms associated with different mental disorders and 17.9% had low self-esteem scores. Low self-esteem was related to high depression scores and a greater number of symptoms related to various disorders. high intensities of distress were associated with areas of greatest social exposure; higher the intensity of distress reported discomfort, greater were the indicators of various mental disorders, severe depression and lower scores on self-esteem. The discussion sought to establish convergent and divergent aspects of those observed in the literature in the area, particularly considering aspects of social cognition and social relations as an important element for building self-esteem and mental health.